Neurodevelopmental Status of Moderate to Late Preterm Infants at 6 Months Corrected Age (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Moderate Preterm (MP) and Late Preterm (LP) infants together comprise more than 80% of all prematurely born infants. Since last decade, there has been growing concern about Neurodevelopmental Abnormality (NDA) in these infants. This study was aimed to assess neurodevelopmental status of moderate to late preterm born neonates and to determine factors associated with adverse neurodevelopmental outcome in a tertiary hospital in Bangladesh.Materials and methods: In this prospective observational study 215 preterm (32 to